A REVIEW OF DIABETES RISK AND SLEEP DURATION: TRENDS IN THE POPULATION AND POTENTIAL MECHANISMS. - Shankar, Anand (Student’s Journal of Health Research Africa, 2023)
Sleep plays a critical role in controlling a variety of metabolic-related physiological processes. As a result, there is strong evidence to support the link between sleep patterns and the risk of diabetes. The risk of diabetes has specifically been linked to inadequate sleep duration and/or sleep restriction in the lab, poor sleep quality, and sleep disorders such as insomnia and sleep apnea. Epidemiological and laboratory studies are included in this study. Diabetes and obesity are both predisposed to behavioral risk factors like increased food intake, impaired judgment, and a higher likelihood of other behavioral risk factors like smoking, sedentary behavior, and alcohol use as well as physiological risk factors like insulin resistance, decreased leptin, increased ghrelin, and inflammation. Obesity is also a significant diabetes risk factor. The evidence relating sleep to diabetes risk is discussed in this review at both the population and laboratory levels.